Advanced youth music ensembles: Experiences of, and reasons for, participation. (August 2013) - Hewitt, Allan; Allan, Amanda
The experiences of 72 adolescent musicians who had been members of an advanced youth symphony orchestra or concert band were investigated. An online survey explored previous participation and the importance of past experiences when making future decisions about participation. Previous experience was very positive. Enjoyment of public performances, a sense of musical satisfaction from participating, and opportunities to meet new people and spend time with other musicians were highly rated. First-time decisions to participate were primarily influenced by positive feedback from friends and peers while ongoing participation tended to be based on the positive experience of the musical and social aspects of participation rather than contextual aspects such as location or the input of significant others such as instrumental teachers or parents.